Frequency and pattern of adult congenital heart disease in a tertiary care cardiac hospital: reasons associated with delayed diagnosis - Ahsan, Aliya Kemal; Sangi, Rumana; Shaikh, Abdul Sattar; Mohammad Mohsin; Saba Mumtaz (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the distribution pattern and possible reasons of delayed diagnosis of congenital heart disease in adult population. Method: The analytical, cross-sectional study was conducted at the Department of Paediatric Cardiology, National Institute of Cardiovascular Diseases, Karachi, from July to December 2021, and comprised patients of either gender aged 18 years and above with congenital heart disease confirmed by echocardiographic examination. Age, gender, weight, height, provincial affiliation, marital status, number of children, if any, duration of disease and New York Heart Association classification were noted on a predesigned proforma. Patterns of congenital heart disease types and reasons behind delayed diagnosis, if noted, were recorded. Data was analysed using SPSS 26. Results: Of the 129 patients, 68(52.7%) were males. The overall mean age was 25.8±9.8 years. Mean age at the time of diagnosis was 12.4±14.8 years. There were 91(70.5%) cases with delayed diagnosis. There was no significant gender difference with respect to delayed diagnosis (p>0.05). Delayed referral 39(42.9%), delayed consultation 22(24.2%), delayed diagnosis by the doctor 21(23.1%), and social factors 9(9.9%) were the most frequent reasons behind delayed diagnosis. Ventricular septal defect was the most frequently defect 38(29.5%), followed by tetralogy of fallot 32(24.8%). Right ventricular dysfunction was the most common complication of delayed diagnosis 35(27.1%). Conclusion: Delayed diagnosis of congenital heart disease was reported in over two-thirds of the cases, with ventricular septal defect being the most frequent type of defect, and delayed referral being the most common reason. Key Words: Congenital heart disease, Diagnosis, Echocardiography, Tetralogy of fallot, Ventricular septal defect.